A case of Sβ+ sickle cell disease diagnosed in adulthood following acute stroke: it's 2021, are we there yet?. Issue 5 (3rd September 2021) - Runge, Ava; Brazel, Danielle; Pakbaz, Zahra
ABSTRACT: In this report, we present a 29-year-old African American female who was brought to a local emergency department after being found unresponsive by her mother. The etiology of her stroke and severe hemolysis remained unknown, despite her mother reporting the patient's history of co-inheritance of sickle cell trait and beta-thalassemia trait, and extensive workup during her prolonged hospitalization. She was diagnosed with sickle cell disease (Sβ+ type) two years after discharge when she was referred to a sickle cell specialist for persistent anemia. Here, we also briefly review the challenges to diagnose rarer subtypes of sickle cell disease (SCD), in this case Sβ+ type, as well as the pathophysiology and current management of stroke in SCD.